STUDY OF THE PROCESS AND AESTHETICS OF LASEM BATIK MOTIFS IN THE “KIDANG MAS” BUSINESS UNIT, REMBANG REGENCY - Salsabila Putri Rahma Hafidza (Eduarts: Jurnal Pendidikan Seni, 2025)
Batik Lasem is a cultural heritage from Lasem District, Rembang Regency, Central Java, Indonesia. Its motifs are the result of cultural acculturation among Javanese, Chinese, and Dutch traditions, forming a distinctive aesthetic that remains relevant today. These aesthetic values are preserved through traditional and sustainable production methods, as practiced by the “Kidang Mas” business unit in Rembang. This study aims to: (1) understand and explain the process of making Lasem batik, (2) explore the diversity of its motifs, and (3) analyze the aesthetic characteristics of Lasem batik produced by “Kidang Mas.” The research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. Data analysis includes data reduction, data presentation, conclusion drawing, and verification. Findings show that the production process in “Kidang Mas” consists of pre-production, production, and post-production stages, with an added "ngrendem" stage to soften the fabric before dyeing. The motifs are categorized into geometric, naturalistic (flora, fauna, and natural elements), and symbolic designs, influenced by the surrounding culture. The aesthetic values of Batik Lasem are reflected in its contemplative nature, symbolism, philosophy, rhythm, balance, and the use of vibrant, characteristic colors, representing the cultural richness of Lasem.